2018
DOI: 10.1007/s10997-018-9438-4
|View full text |Cite
|
Sign up to set email alerts
|

Does municipal ownership affect audit fees?

Abstract: This study analyses whether municipal ownership affects and determines audit fees. Our model of the determinants of audit fees was tested on data from 249 Swedish municipal and 240 private corporations within the real estate industry, thus extending the study of audit fees to hybrid organizations. The statistical analysis was followed up with interviews of five partners from five different audit firms. The result of the study shows that municipal corporations are paying significantly lower audit fees than equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…The regression results support the cost-benefit principle and the risk-benefit equilibrium principle we proposed in the hypothesis development, showing that higher accounting information consistency (smaller value of Consistency) can significantly reduce companies' audit fees. Theoretically and logically, our result is similar to those of existing studies (Cho et al, 2017;Castro et al, 2019;Axén et al, 2019;Smith et al, 2019;Bastos et al, 2021), and it is also supported by research findings from developing countries (Wang et al, 2020;Tsai & Huang, 2020;Li et al, 2020;Chan et al, 2021;Rahayu et al, 2021;Alharasis et al, 2022). Therefore, auditors who audit high-cost or high-risk accounting information (manifested as low consistency) will require a higher audit premium, compensating for their costs or risks and ensuring the accounting information quality and audit quality.…”
Section: Multiple Regression Results and Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…The regression results support the cost-benefit principle and the risk-benefit equilibrium principle we proposed in the hypothesis development, showing that higher accounting information consistency (smaller value of Consistency) can significantly reduce companies' audit fees. Theoretically and logically, our result is similar to those of existing studies (Cho et al, 2017;Castro et al, 2019;Axén et al, 2019;Smith et al, 2019;Bastos et al, 2021), and it is also supported by research findings from developing countries (Wang et al, 2020;Tsai & Huang, 2020;Li et al, 2020;Chan et al, 2021;Rahayu et al, 2021;Alharasis et al, 2022). Therefore, auditors who audit high-cost or high-risk accounting information (manifested as low consistency) will require a higher audit premium, compensating for their costs or risks and ensuring the accounting information quality and audit quality.…”
Section: Multiple Regression Results and Analysissupporting
confidence: 89%
“…In addition, audit fees are subject to other factors. In the area of corporate governance, for the nature of corporate ownership, Axén et al (2019) found that municipal corporations pay significantly lower audit fees than equivalent private companies, mainly due to their lower commercial risks. Smith et al (2019) found that board-level risk committees and more active audit committees may help mitigate the audit fees premium about the risks of breaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the public sector, very few recent studies could be identified. A study by Bradbury (2017) investigated the outsourcing of public sector audits to audit firms, and Axén et al (2019) investigated the comparison of external audit firms' fees for municipalities and equivalent private sector organisations. However, it appears that studies on the link between audit outcomes and audit fees are limited.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Despite municipalities being major economic and social players, studies focusing on the interaction between internal and external auditing among these entities remain relatively small in number compared to the private sector. For municipalities, research has focused on audit fees, audit quality, the audit report lag, procurement practices and determinants of modified audit reports (Axén et al ., 2019; Deis and Giroux, 1992; Marques and Pinto, 2019; Cohen and Leventis, 2013; Paananen, 2016).…”
Section: Introductionmentioning
confidence: 99%